TRIPUSAT PENDIDIKAN SEBAGAI LEMBAGA PENGEMBANGAN TEORI PEMBELAJARAN - -, Al-Muthmainnah (Scolae: Journal of Pedagogy, 2023)
This research is aiming at elaborating the three educational centers which is a concept that gradually and integrated assumes educational responsibility for children. These three centers include education in the family environment, education in the school environment, and education in the community environment. The three centers responsible for education are required to work together comprehensively. This research uses a literature review approach combined with the researcher's reflection method. The literature method utilizes research articles published in various current scientific journals, while the reflection method is based on the knowledge and experience of researchers in recognizing, identifying and responding to student phenomena in various educational institutions. The family environment, which is the first environment and is considered the foundation of a child's education and the beginning of the education that will be pursued later, also plays a major role in personality formation. The school environment is the second environment that children face. Education in the school environment has a foundation, objectives, content, methods and other requirements which are arranged systematically in the form of a curriculum. Therefore, schools are considered the foundation of knowledge. Meanwhile, in society, children will be aware of a number of educational and teaching theories that have been taught in previous educational institutions. Then they will actualize and involve themselves in the community environment. Keywords: three centers of education, development, learning theory